PENGARUH REBUSAN KULIT KAYU MANIS TERHADAP KADAR ASAM URAT PADA LANSIA DI DUSUN BOLOREJO DESA TIRULOR KECAMATAN GURAH KABUPATEN KEDIRI - admin ilkes (STIKES Karya Husada Kediri, 2017)
Gout or often called by uric acid is a heterogenous group of circumstances related to genetic effects on purine metabolism which is characterized uric acid levels in the blood higher than normal. The purpose of this study is to determine the effect of cinnamon bark decoction against uric acid levels on elderly in the Bolorejo Hamlet Tirulor Village Gurah Subdistrict Kediri Regency. The method was used Pre post experiment with no control. Data was collected by checking pre and post after given cinnamon bark decoction, then analyzed using Paired T-Test. The results on 12 respondents before and after treatment obtained by t value 3.490 (p-value = 0.005 ≤ α = 0.05). The conclusion, there was an effect before and after treatment on uric acid levels almost entirely 91.7%. cinnamon bark decoction (eugenol, flavonoids and cinnamaldehyd) could decrease uric acid levels . Cinnamomum bark decoction can be used as an alternative option to overcome the levels of uric acid in elderly.